Advances in Cancer Treatment by Targeting the Neddylation Pathway - Gai, Wenbin; Peng, Zhiqiang; Liu, Cui Hua; Zhang, Lingqiang; Jiang, Hong (Frontiers in Cell and Developmental Biology, 2021)
Developmental down-regulation protein 8 (NEDD8) expressed by neural progenitor is a ubiquitin-like protein that conjugates to and regulates the biological function of its substrates. The main target of NEDD8 is cullin-RING E3 ligases. Upregulation of the neddylation pathway is closely associated with the advance of various tumours, and MLN4924 which inhibits NEDD8 activating enzyme (NAE), has great potential as a new antitumour compound for combination therapy. Here, we summarize the latest progress in anticancer strategies targeting the neddylation pathway and their combined applications, providing a theoretical reference for the development of antitumour drugs and combination therapies.